Exploring Generative AI in Human Resource Management: Opportunities, Challenges, Use Cases, and a UX-Centered Perspective - Ohri, Ijya Bhatnagar (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation examines how generative Artificial Intelligence (AI) affects Human Resource Management (HRM). It focuses on how AI can speed recruitment, personalize employee training, improve performance evaluations, and boost employee engagement and satisfaction. The study uses data and user experience (UX) insights to evaluate how AI tools change important HR processes and what this means for organizations and employees. The findings show that many people recognize AI's ability to automate recruitment tasks like screening resumes. This helps reduce the time it takes to hire and improves candidate diversity. AI tools also make performance evaluations more accurate by providing data-driven insights, which helps to minimize human bias. However, there are challenges like user adoption, integration, and transparency. These issues highlight the need for better UX design to maximize the benefits of AI tools. AI effectively creates personalized learning experiences for employee training and retention. This leads to better knowledge retention and engagement. However, some employees feel that the training is only sometimes relevant or interactive, showing a need for more tailored features and better user engagement. Additionally, AI-driven HR support systems have improved employee satisfaction, especially during onboarding and when accessing HR resources. Still, some neutral responses suggest room for UX design and communication improvement. The dissertation also covers ethical issues like data privacy and algorithmic bias, which need careful management to ensure fair AI use in HR practices. The research highlights the importance of combining AI's analytical abilities with human oversight to build trust and inclusivity. Overall, this study adds to the understanding of AI in HRM by outlining its benefits, challenges, and future possibilities. It provides practical insights for organizations wanting to use AI to improve HR functions while keeping a user-centred approach, emphasising transparency, fairness, and continuous improvement.